Media-expressed tone, Option Characteristics, and Stock Return Predictability - Cathy Yi-Hsuan Chen; Matthias R. Fengler; Wolfgang Karl Härdle; Yanchu Liu (Humboldt-Universität zu Berlin, International Research Training Group 1792 "High Dimensional Nonstationary Time Series", 2019)
We distill tone from a huge assortment of NASDAQ articles to examine the predictive power of media-expressed tone in single-stock option markets and equity markets. We find that (1) option markets are impacted by media tone; (2) option variables predict stock returns along with tone; (3) option variables orthogonalized to public information and tone are more effective predictors of stock returns; (4) overnight tone appears to be more informative than trading- time tone, possibly due to a different thematic coverage of the trading versus the overnight archive; (5) tone disagreement commands a strong positive risk premium above and beyond market volatility.
Keywords: G12; G14; G41; 330; option markets; equity markets; stock return predictability; media tone; topic model